2014
DOI: 10.1002/ijc.29193
|View full text |Cite
|
Sign up to set email alerts
|

The biguanides metformin and phenformin inhibit angiogenesis, local and metastatic growth of breast cancer by targeting both neoplastic and microenvironment cells

Abstract: The human white adipose tissue (WAT) contains progenitors with cooperative roles in breast cancer (BC) angiogenesis, local and metastatic progression. The biguanide Metformin (Met), commonly used for Type 2 diabetes, might have activity against BC and was found to inhibit angiogenesis in vivo. We studied Met and another biguanide, phenformin (Phe), in vitro and in vivo in BC models. In vitro, biguanides activated AMPK, inhibited Complex 1 of the respiratory chain and induced apoptosis of BC and WAT endothelial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
102
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(110 citation statements)
references
References 49 publications
6
102
0
2
Order By: Relevance
“…Millimolar concentrations of metformin stimulated astrocytic glycolysis in a time-and concentration-dependent manner as demonstrated by a doubling of both glucose consumption and lactate production. Metformin-induced stimulation of glycolysis has recently also been reported for rat skeletal muscle [6], human white adipose tissue progenitor cells [8] and mouse astrocytes [32].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Millimolar concentrations of metformin stimulated astrocytic glycolysis in a time-and concentration-dependent manner as demonstrated by a doubling of both glucose consumption and lactate production. Metformin-induced stimulation of glycolysis has recently also been reported for rat skeletal muscle [6], human white adipose tissue progenitor cells [8] and mouse astrocytes [32].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, at least for rats was demonstrated that metformin concentrations in the cerebrospinal fluid are substantially higher than those determined for plasma [16]. For acute experiments in the hour range metformin has frequently been applied to cells in concentrations of 10 mM [6,8]. However, during prolonged incubations less metformin is required to stimulate glycolysis in astrocytes and already 1 mM metformin doubled astrocytic lactate generation within 24 h. It remains to be elucidated whether even micromolar concentrations of metformin would be sufficient to stimulate astrocytic glycolysis during incubations for days or weeks.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Combination of dichloroacetate with metformin was reported to synergistically induce caspase-dependent apoptosis involving oxidative damage (Haugrud et al, 2014). Orecchioni et al (2015) studied the effects of metformin and phenformin on breast cancer using in vitro and in vivo models, and found that phenformin was more effective than metformin in both models. Both drugs were reported to induce apoptosis of breast cancer and the human white adipose tissue (WAT) endothelial cells through the activation of AMPK and inhibition of Complex 1 of the respiratory chain in the in vitro model.…”
Section: Metformin and Cancermentioning
confidence: 99%
“…These data correspond to observations that metformin can increase VEGF expression, intratumoral microvascular density and reduces necrosis thus promoting the angiogenic phenotype and increasing tumorigenic progression. 42 Martin-Montalvo et al 38 supplied male C57BL/6 mice with ad libitum diet with supplementation of 0.1% (1,000 ppm) or 1% (10,000 ppm) of metformin starting from the age of 54 weeks for the remainder of their lives. The mean life span of mice treated with 0.1% of the drug in diet was increased by 5.83% as compared to the relevant control group, whereas the dose 1% was toxic and reduced the mean life span by 14.4%.…”
Section: Discussionmentioning
confidence: 99%